Mirroring the zeitgeist: an analysis of CSR policies in the UK's food, soft drink and packaging industries. Issue 1 (5th October 2020) - Topić, Martina; Bridge, Gemma; Tench, Ralph
Abstract : Purpose: The purpose of this paper is to explore changes in corporate social responsibility (CSR) policies in food, soft drinks and packaging industries to capture changes in CSR implementation given increased environmental activism. The paper takes an exploratory approach in reviewing CSR policy changes to explore to what extent companies change CSR policies with increased environmentalism. Design/methodology/approach: A comparative website analysis was used to analyse CSR policies of companies in the food, soft drinks and packaging industries in the UK. The companies were selected for the analysis based on their annual turnover and 23 companies were analysed (seven for the soft drinks industry, eight for the food industry and eight for packaging industry). Five interviews were conducted with packaging and retail professionals, and the findings were analysed by using thematic analysis, which captured trends in responses. Findings: The findings show that companies are implementing and communicating CSR policies heavily focussed on reducing the environmental impact of their work and matching social debates on human rights, with which traditional CSR policies (corporate governance, supporting local communities and consultation with stakeholders) are fading away. Instead, companies have shifted attention towards the gender pay gap, modern slavery and extensive environmentalism. The interviews with packaging professionals and CSR managers from the retail industry show that the packaging industry designs CSR policies in line with requests from supermarkets, which are, in turn, influenced by consumer activism. Practical implications: This paper shows the circular relationship between media coverage, consumer activism, which comes as a result, and the impact and changes this brings to the industry. To avoid reputation damage, companies should closely follow media debates to pre-empty consumer criticism and activism. Social implications: The findings show that companies are "mirroring the zeitgast" and going with trends to meet consumer expectations, which brings into question the sincerity of CSR policies and revives the criticism of capitalism and raises a question whether CSR is used by companies as a smokescreen that on the outset makes a difference to the society but keeps status quo intact. Originality/value: The paper provides an insight into CSR implementation of three industries that faced heavy criticism from campaigners and the general public for their environmental impact. The paper shows how the CSR policy shifted to match this expectation and thus provides a good ground for studying the evolution of CSR using a case study from three selected industries.